Mangrove Health Index Using MonMang v2.0 Application In Sei Nyirih, Tanjungpinang City - Imelyannari, Arum Rizki; Susiana, Susiana; Amran, Muhammad Anshar (Sangia Research Media and Publishing, 2025)
The mangrove ecosystem is a plant that is closely related to water. Mangroves have an important role in preserving aquatic ecosystems, beaches and even land areas. The important role of mangroves in these waters will of course be directly related to the health condition of mangroves in an ecosystem. Mangrove health is an integral part of sustainable management of mangrove ecosystems. The research carried out on the mangrove ecosystem in the Sei Nyirih water area aims to determine the Mangrove Health Index, Community Structure and Important Value Index. This research method uses Purposive Sampling at three stations with three plots at each station. The results of the research in the Sei Nyirih mangrove area were divided into three categories, namely the Tree Category, Sapling Category and Seedling Category with the types found namely Rhizopora apiculata, Bruguiera gymnorhiza, Xylocarpus granatum, Schyphipora hysrophylacea, Ceriops tagal and Lumnitzera littorea. The Importance Value Index is dominated by the Rhizopora apiculata type in the Tree and Sapling Category, while in the Seedling Category it is the Xylocarpus granatum type. Then the Mangrove Health Index (MHI) obtained from the MonMang V 2.0 Application Station 1 with an average of 67.34% or in the Excellent category, Station 2 with an average of 66.57% or in the Moderate category and Station 3 with an average of 67.62% or in the Excellent category. Meanwhile, the Mangrove Health Index uses Excel Station 1 with an average of 76.07% or in the Excellent category, Station 2 with an average of 74.96% or in the Excellent category and Station 3 with an average of 78.62% or in the Excellent category.